2016
DOI: 10.1007/s00586-016-4708-9
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of unusual entrance of the vertebral artery into the cervical foramen (V2 segment) and its clinical implications

Abstract: To avoid an unexpected VA injury and to improve the efficiency of even routine cervical operations, spinal surgeons should determine whether the patient has a UE-V2S and have a full understanding of the clinical characteristics of this anomaly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…Eskander et al [18] observed a C 4 , C 5 , and C 7 level of entrance in 1.8, 5.6, and 0.6% of their patients and Tellioglu et al [23] in 0.45, 1.84, and 1.84% of their patients, respectively. Entry point in the C 5 vertebra was also the most frequent variation in the study of Kim et al [6], observed in 74.8% of all unusual vertebral artery courses. In this study, entrance of the artery in the C 5 vertebra was the most common variation as well (8% of all patients), followed by entrance in the C 7 vertebra (4%) and the C 4 vertebra (2%).…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…Eskander et al [18] observed a C 4 , C 5 , and C 7 level of entrance in 1.8, 5.6, and 0.6% of their patients and Tellioglu et al [23] in 0.45, 1.84, and 1.84% of their patients, respectively. Entry point in the C 5 vertebra was also the most frequent variation in the study of Kim et al [6], observed in 74.8% of all unusual vertebral artery courses. In this study, entrance of the artery in the C 5 vertebra was the most common variation as well (8% of all patients), followed by entrance in the C 7 vertebra (4%) and the C 4 vertebra (2%).…”
Section: Discussionmentioning
confidence: 78%
“…Vertebral artery variations are also not an unusual finding. The most usual entry point of the artery in the spine is the C 6 vertebra [22,23], but entrance of the artery in the C 4 , C 5 , and C 7 vertebra has been also reported [5,6,18,23]. Wakao et al [5] observed a C 4 level of entrance in 1.1%, a C 5 Table 4 Coexisting variations of the foramen transversarium in patients exhibiting asymmetry in the vertebral artery level of entrance in 6.2%, and a C 7 level of entrance in 1.5% of their patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations